Neither Sustainable Nor Inclusive: A Political Economy Of Agricultural Policy And Livelihoods In Malawi, Tanzania And Zambia - Ofori, Alesia Dedaa; Mdee, Anna; Chasukwa, Michael; Manda, Simon (My University, 2022)
The food crisis of 2007/8, alongside rapid population growth, and the uncertainties of climate change propelled African agricultural transformation back into the development mainstream. New narratives of ‘climate-smart agriculture’ and ‘sustainable intensification’ underlie this contemporary transformation. We present a political economy analysis of agricultural policy and livelihoods in Malawi, Tanzania and Zambia, and use this to assess the challenge of achieving ‘sustainable and inclusive intensification’. We find little evidence that agricultural institutions have the capacity to deliver sustainable intensification in agriculture, or that agricultural policy drives changes in agricultural livelihoods that will make them either more sustainable or inclusive.
Keywords: Political economy; Sustainable intensification; Environmental Politics